THE USE OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) LEARNING MODEL ON THE STUDENTS’ READING COMPREHENSION IN LEARNING ENGLISH - Zaenuddin, Nur Hikma; Asriati, Siti; Hafid, Hilda (English Language Teaching Methodology, 2024)
This study aims to see the application of the Cooperative Integrated Reading and Composition (CIRC) learning model to students' reading comprehension in learning English. This study used a pre-experimental method. Data collection techniques were carried out through pre-test and post-test. The research was conducted at SMP Negeri 13 Makassar, with the population being class VIII students at SMP Negeri 13 Makassar. The results of this study indicated that for the main idea the average pre-test score of students before being treated with reading comprehension is 5.92 and the average post-test score of students after being treated with reading comprehension is 8.08. The significance of the main idea between the pre-test and post-test was 36.48%. Meanwhile, for the conclusion, the average pre-test score of students before being treated with reading comprehension was 5.6 and the average post-test score of students after being treated with reading comprehension was 8.32. The significance of the main idea between the pre-test and post-test was 48.57%. The results of data analysis showed that the increase in students' reading ability after being treated using the CIRC learning media increased the results quite significantly. = 0.05 with degrees of freedom (df) = 24 which shows the t-test value of 13.55 and t-table = 2.640. Based on the results of the post-test data obtained as the final result, this study provides a fairly good improvement. Finally, it can be concluded that the use of CIRC learning media is able to give a good influence in learning English, especially on reading comprehension.